Depressive states and familiar atmosphere in children with poor school performance - Bulnes Bedón, Marío (1998)
In this research infant depression is studied in relation with life quality (instead of family atmosphere), in students with low school achievement in a sample of 372 of both genders, using the de Depression Questionnaire for children by Lang e Ysher; and the Test of Life Quality from Olson and Barnes, finding higher levels of depression in the students with more affectivity, low self-esteem and difficulty ill social interaction.